As relações entre o desenho e o desenvolvimento da consciência na educação infantil à luz da Teoria Histórico-Cultural - Boriollo, Beatriz de Cássia (2022)
This is a theoretical research, based on Historical-Cultural Theory, to answer the question: what is the contribution of Historical-Cultural Theory for the comprehension of the relationship between the development processes of the drawing and the child’s consciousness in the children’s education? The aim was to identify the underpinnings of the Historical-Cultural Theory necessary to relate the development of the drawing and the child’s consciousness, as well as its possible implications in the teaching practice. Therefore, through the genetic-experimental method of Historical-Cultural Theory and based on theoretical-bibliographic research, we discussed the necessity of the teachers to maximize, intentionally, the development of children’s drawings, to provide the development of higher psychological functions. As specific goals, we seek: to conceptualize the underpinnings of the drawing in the Vygotskian theory and find fundamental issues (guidelines originated from reflective abstractions) to comprehend the development process of the drawing and the child’s consciousness, and its possible implications in the pedagogical practice; to discuss the teacher’s role as enhancer of the drawing’s development. As from the immersion in the historical reality of our research subject, we identified in the drawing categories and consciousness, the analysis guidelines of data in light of Historical-Cultural Theory. In other words, the school’s role in children’s education, aesthetic and artistic education; the possibilities a teacher in children’s education of creating meaningful contexts in his/her pedagogical practices, intentionally, to the development process of the drawing and the child’s consciousness; the relationship of the higher psychological function of the drawing with the other higher psychological functions; the possibilities of the drawing also taking other roles in the child’s development and the relationships between the drawing development and the child’s consciousness development in the children’s education. The results proved our thesis: the teacher’s intentionally planned action for an aesthetic and artistic education, guided to the development process of the higher psychological functions, meaningful to a child, can promote and maximize the movement between the drawing development and the child’s awareness raising process.